Preliminary results of botulinum toxin A switch after first detrusor injection failure as a treatment of neurogenic detrusor overactivity. Issue 2 (18th December 2014) - Peyronnet, Benoit; Roumiguié, Mathieu; Castel‐Lacanal, Evelyne; Guillotreau, Julien; Malavaud, Bernard; Marque, Philippe; Rischmann, Pascal; Gamé, Xavier
ABSTRACT: Aims: To assess the results of onabotulinum toxin detrusor injections when abobotulinum toxin detrusor injection failed. Methods: Twenty‐six patients, 15 women and 11 men, mean age 40.8 ± 12.7 years old, in whom a first injection of 750 U abobotulinum toxin in 20 sites failed in treating neurogenic detrusor overactivity, received onabotulinum toxin 300 U detrusor injections in 30 sites. Neurologic conditions were spinal cord injury in 14 cases, multiple sclerosis in nine, myelomeningocele in two and myelitis in one. Mean time between the two injections was 5.6 ± 1.4 months. Before and 6 weeks after each injection, patients carried out a 3‐day bladder diary and had urodynamics. The success was defined as the combination of a clean intermittent self‐catheterization number under 8 per 24 hr, urgency, urinary incontinence and detrusor overactivity relief. Results: Out of 26 patients, the second injection was successful in 15 (57.7%). While the first injection of 750 U abobotulinum toxin had no impact at all, after 300 U onabotulinum toxin injection, the number of clean intermittent self‐catheterization decreased significantly (11.3 ± 2.1 vs. 6.4 ± 1.9, P = 0.01), 17/26 (65.4%) patients achieved continence, urgency was relieved in 18/26 (69.2%) and detrusor overactivity in 15/26 (57.7%). Conclusions: In case of failure after a first detrusor injection of abobotulinum toxin, switching for onabotulinum toxin is efficient. Further investigations should be performed to assess whether the replacement of onabotulinum toxin by abobotulinum toxin provides the same results. Neurourol. Urodynam. 35:267–270, 2016 . © 2014 Wiley Periodicals, Inc.